Hydrothermal synthesis of nano ZrO2 powders - Duran, Cihangir; Yu, Jia; Sato, Kimiyasu; Hotta, Yuji; Watari, Koji (Trans Tech Publications Ltd, 2006)
Hydrothermal synthesis of nano ZrO2 powders were carried out at a temperature range of 100 to 200 degrees C, using zirconium solution. Formation of ZrO2 formation was accelerated with temperature and precipitation of ZrO2 took place directly from the solution. XRD analysis revealed that monoclinic ZrO2 was formed at all conditions. Crystallite size was found to range from 2.6 to 4 nm. Mean particle size increased from 93 nm at 135 degrees C to 125 nm at 200 degrees C after reaction time of 2 h.
3rd International Symposium on the Science of Engineering Ceramics (EnCera 2004) -- OCT 31-NOV 03, 2004 -- Osaka, JAPAN
Keywords: hydrothermal synthesis; nano powders; ZrO2